Peril trek - Brand, Max (New York City Leisure Books, 2003)
Reata finally escapes from the clutches of criminal mastermind Pop Dickerman and is hired by Bob Clare, a desperate man in need of protection.
The man who followed -- The boy who found Christmas -- The peril trek: a Reata story.
83057
Keywords: Western; Western stories